Game-Based Learning Approach to Enhance Tactical Understanding and Motivation in School Football Physical Education - Sandi Ahmad Pratama; Linda Susila; Erika Mc Clintock (INSPIREE: Indonesian Sport Innovation Review, 2026)
Background: Traditional football teaching in school physical education often emphasizes technical drills and skill repetition, which can lead to reduced student engagement and limited development of tactical understanding. Game-Based Learning (GBL), particularly through the Teaching Games for Understanding (TGfU) model, offers an alternative approach that prioritizes tactical awareness and decision-making within authentic game contexts. Purpose: This quasi-experimental study examined the effectiveness of a GBL approach in improving tactical understanding and intrinsic motivation among secondary school students in football physical education classes in Kabupaten Dompu, Nusa Tenggara Barat, Indonesia. Methods: Eighty-four students (mean age = 14.6 ± 1.2 years; 52 males, 32 females) from two secondary schools participated in an 8-week intervention (16 sessions, 2×/week). The experimental group (n=42) received GBL-based instruction using modified small-sided games and tactical questioning, while the control group (n=42) followed traditional skill-drill methods. Tactical understanding was assessed using the Game Performance Assessment Instrument (GPAI), and motivation was measured using the Sport Motivation Scale (SMS) adapted for physical education. Data were analyzed using paired t-tests, ANCOVA, and Cohen's d effect sizes. Results: The GBL group demonstrated significantly greater improvements in tactical understanding (decision-making: 42.3%; skill execution: 31.8%; support: 38.5%) compared to the control group (15.2%, 18.4%, 12.7% respectively; all p < 0.001). Regarding motivation, the GBL group showed significant increases in intrinsic motivation (d = 1.24, p < 0.001), identified regulation (d = 0.89, p < 0.001), and decreased amotivation (d = -1.02, p < 0.001), while the control group showed minimal changes. ANCOVA revealed significant between-group differences favoring GBL on all measures (F-values ranging from 32.45 to 58.72, all p < 0.001, partial η² = 0.28-0.42). Conclusions: The GBL approach using TGfU principles significantly enhanced both tactical understanding and autonomous motivation in secondary school football education. These findings support the implementation of game-centered pedagogies in Indonesian physical education contexts and suggest that GBL may address common challenges of student disengagement in traditional skill-focused instruction. Future research should explore long-term retention effects and implementation across diverse cultural and educational settings.